KONSEP EPISTEMOLOGI AKAL DALAM PERSPEKTIF ISLAM - Nur Shadiq Sandimula (Institut Agama Islam Negeri (IAIN) Manado, 2019)
This article trying to analyze the concept of intellect according to Islamic scholar (ulama). Based on a library research, this research uses a descriptive analysis method to derive the data and information from the books of Islamic authoritarive scholar about the topic. The research shows that intellect according to Islamic scholar is an accidental abstract potential that placed in the heart, and the one who posses it have a capabililty to contemplate about a reality and meaning of everything and at once to justify and consider the value of the meaning and reality itself. Intellect is not just a cognitive faculty but also intuitive capability, it is not just a rational analysis, but also moral choice, it is not just a conceptual faculty towards empirical world, but also spiritual capability towards sprititual and ideal or imaginal world. For the conclusion, Islamic way of thinking is integrative or unified based on Tauhidic concept. In Islamic concept of rational and intellectual thinking, there is no dichotomy or separation between internal (batin) and external (zahir) reality, cognitive and intuitive, material and spiritual, rational and moral, knowledge and deed, sacral and profane, ideality and reality, and also this world and the hereafter. This concept is known as the Tauhidic Concept of Knowledge.Keywords: Epistemology; intellect; cognitive; intuitive Artikel ini hendak menganalisis pendapat para ulama Islam berkenaan dengan konsep akal. Penelitian ini merupakan penelitian pustaka (library research), penelitian ini menggunakan metode analisis deskriptif atas data dan informasi yang diperoleh dan diderivasi dari buku-buku para ulama Islam yang otoritatif berkenaan dengan topik tersebut. Penelitian menunjukkan bahwa akal menurut ulama Islam adalah suatu potensi abstrak berwujud aksiden yang bertempat pada hati yang dengannya ia dapat melakukan kontemplasi dan perenungan terhadap hakekat dan makna sekaligus justifikasi dan pertimbangan mengenai nilai yang baik maupun yang buruk. Akal bukan sekedar suatu kepahaman secara kognitif namun juga mengandung unsur intuitif, bukan sedekar analisis rasional namun termasuk juga pilihan moral, dan bukan sekedar kemampuan konseptual terhadap alam fisik namun juga merupakan kemampuan spiritual terhadap alam metafisik. Kesimpulannya, Cara berpikir dalam Islam bersifat integratif atau terunifikasi berdasarkan konsep tawhid Islam tidak mengenal dikotomi atau pemisahan antara aspek internal (batin) dan eksternal (lahir), kognisi dan intuisi, material dan spiritual, rasional dan moral, ilmu dan amal, sakral dan profan, idealitas dan realitas, serta dunia dan akhirat.Kata kunci: Epistemologi; akal; kognitif; intuitif